A Hybrid Approach for Treating Recurrent Renal Cell Carcinoma (RCC) in a Single Kidney with a Tethered Ureter - Carter, Nicole; Al-Shawi, Modher; Royce, Peter; O’Brien, Andrew; Clements, Warren (Journal of Clinical Interventional Radiology ISVIR, 2021)
This case highlights a hybrid treatment model used successfully in a patient with complicated recurrent renal cell carcinoma (RCC), following partial nephrectomy, in the context of a single kidney. Scar tissue from previous surgery tethered the ureter to the margin of the lesion and combined with obesity, rendered simple percutaneous intervention challenging. The patient was ultimately successfully treated using a hybrid approach of open surgical access, ureterolysis, and intraoperative ultrasound-guided radiofrequency ablation. This approach optimized the volume of conserved normal renal parenchyma and eliminated the need for postoperative dialysis treatment, with no recurrence at 13 months follow-up.
Keywords: RCC; ablation; ureterolysis; single kidney; trauma